1999
DOI: 10.1038/sj.jhh.1000824
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of elevated blood pressure as an estimate for hypertension in Aydın, Turkey

Abstract: Background: Hypertension is an important public health problem, with some variability of its epidemiological properties in different populations. Objectives: The purpose of this study was to estimate the prevalence of hypertension and to determine the hypertension awareness, treatment and control rates in Aydın, a Turkish province. Methods: Of 1600 coincidentally selected people aged over 18 years in Aydın, 1480 (92.5%) had their blood pressure (BP) measured and answered a standard questionnaire in 1995. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 17 publications
4
14
1
2
Order By: Relevance
“…Similar results have also been reported in studies conducted in Turkey (10,12,13,22). HT prevalence was higher in older ages also in the studies conducted by Arslantaş et al (22) (>50 years old, 59.5%), and Lai et al (26) (>60 years old; 53.09% in men, 56.06% in women).…”
Section: Womensupporting
confidence: 78%
See 2 more Smart Citations
“…Similar results have also been reported in studies conducted in Turkey (10,12,13,22). HT prevalence was higher in older ages also in the studies conducted by Arslantaş et al (22) (>50 years old, 59.5%), and Lai et al (26) (>60 years old; 53.09% in men, 56.06% in women).…”
Section: Womensupporting
confidence: 78%
“…Although in various studies conducted in Turkey and other countries have shown that, the prevalence of HT was higher in women than men (7,10,12,13,22,23) in some other studies HT prevalence is more prevalent in men than women (8,24). In our study, gender was a significant risk factor for HT; women had more HT risk than men (31.3% in women, 14.1% in men).…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…Cetinarslan et al found that 50.8% of men and 52.5% of women were hypertensive by using the level of 160/90 mm Hg in subjects ≥ 60 years of age in a different part of Turkey (15). In another study from Turkey, 30.1% of men and 51.4% of women older than 60 years of age were found to be hypertensive [14]. It has been well known that the prevalence of hypertension increases with age.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the prevalence of diabetes is increasing worldwide. Although few national or regional studies have been undertaken on the prevalence of hypertension in Turkey, a high prevalence of hypertension has been reported (29.6% to 33.4%) in the adult population [6,11,14]. However, there is little data on the prevalence of hypertension and other cardiovascular risk factors in the elderly.…”
Section: Introductionmentioning
confidence: 96%